Konsep Sunnah dalam Perspektif Ahmad Amin - Umar, Atho’illah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2018)
The earliest discourse on hadith revolves around the attempts to record in a written material, which in several accounts of Prophetic traditions are banned to write. This issue further becomes the center of the problem on the authority and authenticity of the hadiths where many scholars have paid attention to its discussion. This article was an attempt to reconceptualize a theory of hadith criticism initiated by Ahmad Amin. Through his book Fajr al-Islam, Amin, among others, questioned the originality of the hadith after the death of the Prophet. He recounted the concept of sunnah by questioning its authenticity after the death of the Prophet. This article also presents a theoretical criticism to some extend gives some responses to those who contend the concept of ‘adalat al-sahabah, a concept whose existence has been agreed upon as a measure of hadi>th measurement by scholars of muhaddithin.